ELABORASI PENYUSUNAN LAPORAN KEUANGAN KONSOLIDASI KE DALAM NILAI SYARIAH ISLAM - Bambang Waluyo; Ali Masjono (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2012)
This study aimed to obtain a design of the process of preparing the consolidated financial statements associated with syariah values in Islam, especially the value of fairness and honesty. The consolidated financial statements are designed to present the results of operations and financial position of the company and its subsidiaries. In the process, it will be clearly seen an effort to avoid injustice and dishonesty, because things are "suspected" as potentially able to "cheat" its readers in a way the elimination of the efect through adjusting entries and elimination. So that these process will be in accordance with the Quran and the HadithDOI: 10.15408/aiq.v4i2.2574